Chris Hann and Jonathan Parry (eds.), Industrial Labor on the Margins of Capitalism: Precarity, Class, and the Neoliberal Subject - Hazl, Polona (Lidé města, 2021)
A review of the book by Chris Hann and Jonathan Parry.